Big goals the science of setting them, achieving them, and creating your best life - Miller, Caroline Adams 1961- (Wiley, 2025)
"Big Goals: The Science of Setting Them, Achieving Them, and Creating Your Best Life delves deeply into effective goal setting practices for both personal growth and corporate excellence, empowering individuals across all ages to pursue their ambitions with a newfound sense of confidence and mastery. Readers of this book will gain a nuanced understanding of the little-known science of goal setting, with practical tools and unique worksheets to use on their goal-achieving journey"--
Includes index. - Description based on online resource; title from digital title page (viewed on December 02, 2024)
Keywords: Goal (Psychology); Success; Self-actualization (Psychology); Succès